The effect of high carbohydrate meals with different glycemic indices on recovery of performance during prolonged intermittent high-intensity shuttle running - Erith, S.; Williams, C.; Stevenson, E.; Chamberlain, S.; Crews, P.; Rushbury, I. (International Journal of Sport Nutrition and Exercise Metabolism, 2006)
This study examined the effect of high carbohydrate meals with different glycemic indices (GI) on recovery of performance during prolonged intermittent high-intensity shuttle running. Seven male semi-professional soccer players (age 23 ± 2 y, body mass [BM] 73.7 ± 9.0 kg and maximal oxygen uptake 58 ± 1.0 mL · kg-1 · min-1) participated in two trials in a randomized cross-over design. On day 1, the subjects performed 90 min of an intermittent high-intensity shuttle running protocol [Loughborough Intermittent Shuttle Test (LIST)]. They then consumed a mixed high carbohydrate recovery diet (8 g/kg BM) consisting of either high (HGI) (GI: 70) or low (LGI) (GI: 35) GI foods. Twenty-two hours later (day 2) the subjects completed 75 min of the LIST (part A) followed by alternate sprinting and jogging to fatigue (part B). No differences were found between trials in time to fatigue (HGI 25.3 ± 4.0 min vs. LGI 22.9 ± 5.6 min, P = 0.649). Similarly, no differences were found between trials for sprint performance and distance covered during part B of the LIST. In conclusion, the GI of the diet during the 22 h recovery did not affect sprint and endurance performance the following day.